Disiplin Ditinjau dari Konsep Diri pada Siswa SMA Ahmad Yani Kota Medan - Diana Rores Tandiono; Diny Atrizka; Rizky Nanda Akbar (Universitas Muhammadiyah Jember, 2020)
The individual's perception of himself can form a self-image that will be reflected in his behavior. As a student, the better the self-concept that is built, the students will behave like students who can be role models. This study aims to determine the relationship between self-concept and discipline. The hypothesis proposed in this study is that there is a positive relationship between self-concept and discipline. The research subjects used in this study were 146 students of SMA X Binjai City. Hypothesis testing in this study uses Pearson Product Moment correlation with the help of SPSS 20 for Windows. The results of data analysis showed a correlation coefficient of 0.549 and a significance value of p 0.001. Based on the results of this study, it can be concluded that the research hypothesis is acceptable, that is, there is a positive relationship between self-concept and discipline..